A novel internal fixation technique for the treatment of olecranon avulsion fracture - Hongfei Qi; Zhong Li; Teng Ma; Bing Du; Cheng Ren; Yibo Xu; Qiang Huang; Kun Zhang; Yao Lu; Ming Li (Frontiers in Surgery, 2023)
ObjectiveTension band wiring and proximal ulnar plate fixation are commonly used fixation methods for olecranon fractures. However, they may not be suitable for repairing proximal olecranon avulsion fractures. In this study, we present a novel fixation technique for the treatment of proximal avulsion fractures, which is a T-shaped plate combined with a wire.Materials and methodsBetween March 2016 and May 2020, surgery was performed on 16 patients with proximal olecranon avulsion fractures by using a T-shaped plate combined with a wire fixation at our hospital. The parameters followed were fracture healing time, elbow range of motion (ROM), related functional scores (the Mayo score and the DASH score), and complications related to internal fixation.ResultsThe average follow-up period was 17 (14–21) months and fractures had healed in all patients included in the study, with an average fracture union of 9.25 (8–12) weeks. No patient reported fixation failure, serious infection, or revision surgery. The average ROM of the elbow joint was 123° (120–135°). The Mayo score was excellent in 11 patients and good in 5. The average DASH score was 17.75 (12–24).ConclusionOlecranon avulsion fractures were fixed with a T-shaped steel plate combined with a steel wire, which can be used for early functional exercise and for achieving good final functional results. This method can provide stable fixation, especially in elderly patients with osteoporosis.